Emotional Connectedness to Nature Is Meaningfully Related to Modernization. Evidence From the Meru of Kenya - Marczak, Michalina; Sorokowski, Piotr (Frontiers in Psychology, 2018)
The aim of this study was to investigate an affective relationship with the natural environment in a non-western society and to determine its links with modernization. Emotional connectedness to nature, a significant predictor of nature-protective behavior, was assessed in a sample of 99 members of the Meru people of Kenya, recruited in places supposedly varying regarding their level of modernization: small market towns, farming villages and a remote pastoralist settlement in the bush. The participants answered questions concerning their level of emotional affinity toward the natural environment and their lifestyle. The results show that feelings toward the natural environment in the studied population were, in general, positive. Such findings support the universality of the Biophilia hypothesis and are promising in the light of extant literature on the links between connectedness to nature and concern for the natural environment. Surprisingly we also found that a more traditional lifestyle was negatively related to emotional connectedness to nature. These findings suggest that contact with nature under conditions of direct dependence on the natural environment may have a different influence on people’s feelings toward nature than in the west. Contrary to the common view, we conclude that the impact of modernization on non-western people’s affective relationship with nature might have been unduly demonized.